The role of technology adoption in shaping employee performance - Jacobis, Riedel; Rozaq, Khoirur; Husain, Muhammad; Ramadhan, Dyandra Armyta; Ramadhani, Bima Yatna (Jurnal Ilmu Manajemen, 2024)
The flow of change in information technology is developing very quickly and rapidly. These changes have a big impact on human resources. Human resources must improve their competencies and adapt to technological advances. Adaptation is mandatory so that organisations are not crushed by technology itself. Drastic environmental changes and intense competition will place higher demands on a person’s adaptability and impact the ability to generate new ideas useful in organisational activities and services, namely innovative work behaviour. The research analyses the impact of innovative work behaviour on employee performance through adaptive technology as a mediating variable. A total of 200 employees tasked with serving Population and Civil Registration data for the City of Surabaya were respondents in this research. This research is explanatory, and the data collected will be processed using structural equation modelling (SEM) analysis techniques. This study provides results that innovative work behavior significantly affects technology adoption. In addition, innovative work behaviour significantly positively affects employee performance. This study also implies that technology adoption influences employee performance and mediates innovative work behaviour and employee performance.